2006
DOI: 10.1016/j.febslet.2006.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Ferredoxin/ferredoxin–thioredoxin reductase complex: Complete NMR mapping of the interaction site on ferredoxin by gallium substitution

Abstract: The reduction of ferredoxin-thioredoxin reductase (FTR) by plant-type ferredoxin plays an important role in redox regulation in plants and cyanobacteria. Nuclear magnetic resonance (NMR) was used to map the binding sites on Synechocystis ferredoxin for FTR. A gallium-substituted structural analog of this [2Fe-2S] ferredoxin was obtained by reconstituting the apoprotein in a refolding buffer containing gallium. For the first time, the complete interaction interface of a [2Fe-2S] ferredoxin with a target enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
(42 reference statements)
3
18
0
Order By: Relevance
“…Recent NMR chemical shift mapping studies of the Fdx-FTR interaction (303) are consistent with the previous results obtained by differential chemical modification (57) and also with the crystal structure of the Fdx-FTR complex (50). The results emphasize the dependency of the interaction on polar as well as nonpolar residues, the latter forming a hydrophobic core.…”
Section: Fig 3 Multiple Sequence Alignment Of the Catalytic Subunitsupporting
confidence: 79%
See 1 more Smart Citation
“…Recent NMR chemical shift mapping studies of the Fdx-FTR interaction (303) are consistent with the previous results obtained by differential chemical modification (57) and also with the crystal structure of the Fdx-FTR complex (50). The results emphasize the dependency of the interaction on polar as well as nonpolar residues, the latter forming a hydrophobic core.…”
Section: Fig 3 Multiple Sequence Alignment Of the Catalytic Subunitsupporting
confidence: 79%
“…This conclusion was supported by mutagenesis experiments in which the replacement of this C-terminal glutamate residue resulted in a protein incapable of reducing FTR (129). These observations have been corroborated and extended by the recent structural studies (50,303) discussed below. Work during the past several years has also added a new dimension to the function of Fdx.…”
Section: A Ferredoxinsupporting
confidence: 71%
“…Interactions between PetF and various redox partners usually involve three polypeptide motifs (28) -Glu 123 in PetF of C. reinhardtii. These three motifs contain highly conserved acidic residues that direct the first stages of complex generation dominated by electrostatic attraction and intermolecular salt bridge formation (22,29,30).…”
mentioning
confidence: 99%
“…Our recent NMR study identified the bindingi nterface of PetF with HydA1 from C. reinhardtii. [15] Apart from the study of the interaction with ferredoxin thioredoxin reductase, [14] none of theseN MR spectroscopic investigations provided information about the important residues coordinating and surrounding the [2 Fe-2 S] cluster.B ecause of the proximity of these residues to the cluster, their nuclear spinsr elax quickly,a nd their NMR signals become broad or undetectable. This paramagnetic relaxation enhancement (PRE) can be avoided by substitution of the paramagnetic iron with diamagnetic gallium(III).…”
mentioning
confidence: 99%
“…(FNR), [13] and ferredoxin thioredoxin reductase [14] has been identified by NMR-titration experiments. Our recent NMR study identified the bindingi nterface of PetF with HydA1 from C. reinhardtii.…”
mentioning
confidence: 99%